Paint the town green - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Urban agriculture Video available in English, Arabic, French or Spanish. RUAF, Netherlands. 2002. System VHS/NTSC. Duration: 45 minutes. With story book, 34 pp. Price available on request